Portfolio theory, 25 years after : essays in honor of Harry Markowitz - Markowitz, H.; Elton, Edwin J.; Gruber, Martin Jay (Amsterdam ; New York : North-Holland Pub. Co. ; sole distributors for the U.S.A. and Canada, Elsevier North-Holland, 1979)
The book covers some areas of research which have been an outgrowth of Markowitz's pioneering work on portfolio theory.
Volume 11.
Includes biliographies.
rua 13/12/16.
Loans
Keywords: Investment analysis